El control interno y su relación con la gestión de las pequeñas y medianas empresas en la región de Loreto durante el periodo 2021 - Rios Blengeri, Allison Esther (2023)
The present investigation explored the internal relationship between control and business management of small and medium-sized enterprises (SMEs) in the Loreto region in 2021. Using Spearman's Rho influence coefficient, the study revealed a moderate positive influence between the effectiveness of internal control and the performance of business management. In addition, a positive, albeit slight, relationship was identified between the perception of profitability and compliance with procedures. Surprisingly, a modest connection emerged between perceived operating efficiency and the assessment of internal control training. These results underline the relevance of internal control in the operations and financial success of SMEs. It is recommended that companies strengthen their internal control systems, invest in regular training and promote a culture of adherence to internal controls to optimize management and profitability. The research contributes to the existing literature by providing specific insights into the context of SMEs in the Loreto region, highlighting the critical importance of internal control in effective business management.